Laennec Bluetooth Untuk Pemeriksaan Denyut Jantung Janin - Eko Nugroho; Wijayanti Wijayanti; Noradina Rahmawati (Jurnal Rekayasa Proses dan Industri Terapan, 2023)
FHR assessment aims to detect early fetal emergencies that can cause death. Laennec is a technology-based tool for monitoring fetal well-being to gather information and identify pathological conditions in the fetus through assessment. The Covid 19 pandemic, which requires maintaining a minimum distance of 1 meter from patients, requires the design of Laennec Bluetooth technology. The purpose of this study for the purpose of this study was to design a bluetooth laennec for examining the fetal heart rate. The method of this research is research and development, namely the Arduino Uno-based Laennec Bluetooth design displays the number of fetal heartbeats (FHR) in real time and continuously in Beats per Minute (BPM) size on the LCD screen attached to the device and can also be displayed on an Android smartphone via applications that are already installed in it which is connected via bluetooth. The monitoring system is designed to automatically monitor and measure FHR. Measurement of FHR uses the MAX4466 Sensor and Arduino Uno as a data processor. Laennec Bluetooth testing by comparing the measurement results with the original Laennec which is made of aluminum by comparing the error values. Based on the test results on 5 pregnant women with a gestational age of more than 20 weeks as a sample conducted by Lennec Bluetooth and measurements made directly with Laennec, the average percentage error was 0.31%. The Bluetooth range on Laennec Bluetooth is a maximum of 14 meters because at the time of the inspection it was in a closed room which was insulated by a wall.